Pengembangan Model Otonomi Neara dalam Pelaksanaan Otonomi Daerah Berdasarkan Sistem Sosiobudaya Lokal di Sumaterabarat dan Bali - Asrinaldi A; Yoserizal Yoserizal (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2009)
This is paper aims to describe the completion of local autonomy based on local culture system in West Sumatera and Bali Province. Beside that, this paper also tries to find out the role of state which depicts state autonomy in implementation of government functions at lowest level, such as nagari in West Sumatera and Desa Pakraman in Bali. Although the local culture system could be applied in local autonomy, yet the modern government system which is introduced by state has affected local culture system at the lowest level. In this context, state autonomy has been involved in fusing local culture system into modern government system so that performing of local democracy declines.